2019
DOI: 10.15666/aeer/1706_1326313271
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF DIFFERENT MIXTURE RATIOS AND HARVEST PERIODS ON GRASS QUALITY OF TRITICALE (xTRITICOSECALE WITTMACK) – FORAGE PEA (PISUM SATIVUM L.) INTERCROP

Abstract: Seydosoglu -Bengisu: Effects of different mixture ratios and harvest periods on grass quality of triticale (xTriticosecale wittmack)forage pea (Pisum sativum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Statistical analysis confirmed a significant impact of the experimental factors and their interaction on dry matter digestibility and organic matter digestibility of field pea/spring triticale mixtures (Figs 1 and 2). Results of the study reported here agree with claims made Under the conditions of the experiment reported here, after harvest of mixtures was delayed from the stage of field pea flowering to field pea flat green pod, there was observed a significant drop in dry matter digestibility and organic matter digestibility, which is concurrent with reports by other authors [Ayub et al 2008, Seydosoglu and Bengisu 2019, Piltz et al 2021]. In the current work, an interaction was confirmed, which revealed that the highest dry matter digestibility and organic matter digestibility were for field pea and field pea/spring triticale mixtures containing 75% + 25% and 50% + 50% of the respective components and harvested at both harvest stages.…”
Section: Resultssupporting
confidence: 93%
“…Statistical analysis confirmed a significant impact of the experimental factors and their interaction on dry matter digestibility and organic matter digestibility of field pea/spring triticale mixtures (Figs 1 and 2). Results of the study reported here agree with claims made Under the conditions of the experiment reported here, after harvest of mixtures was delayed from the stage of field pea flowering to field pea flat green pod, there was observed a significant drop in dry matter digestibility and organic matter digestibility, which is concurrent with reports by other authors [Ayub et al 2008, Seydosoglu and Bengisu 2019, Piltz et al 2021]. In the current work, an interaction was confirmed, which revealed that the highest dry matter digestibility and organic matter digestibility were for field pea and field pea/spring triticale mixtures containing 75% + 25% and 50% + 50% of the respective components and harvested at both harvest stages.…”
Section: Resultssupporting
confidence: 93%
“…Triticale is a hybrid of wheat and rye, and an alternative cereal developed for marginal areas and resistant to drought and cold. Previous studies indicated that higher yield and forage quality can be obtained by cultivation of vetch with cereals compared to pure cultivation of vetch species (LITHOURGIDIS et al, 2011;SEYDOSOGLU et al, 2020). However, Ciência Rural, v.52, n.2, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Silage not only meets the green feed needs of ruminants but also protects the nutritional value by reducing the an-In order to eliminate the lack of quality roughage, the cultivation of mixed fodder plants has become widespread recently. Mixed fodder planting is the cultivation and harvesting of two or more plant species together in the same area and simultaneously (Seydosoglu and Bengisu 2019). These mixes help increase feed production by improving water and soil quality in that area.…”
mentioning
confidence: 99%